Identification of resistance germplasm in sesame (Sesamum indicum) against phyllody disease: Identification of resistance germplasm in sesame (Sesamum indicum) against phyllody disease - K N GUPTA; SHIVANI NAGPURE; A K PANDAY; RAJNI BISEN (Journal of Oilseeds Research, 2023)
Sesame phyllody is an important disease caused by a phytoplasma and is transmitted by a leaf hopper called Orosius albinctus. The affected plants become stunted and floral parts are modified in to leafy structures bearing no fruits and seeds causing yield loss up to 33.9 per cent. 3700 accessions of sesame germplasm were screened for resistance against phyllody disease during kharif 2021 under natural field condition. Results showed that most of the accessions were susceptible to phyllody and only 61 showed some resistance and disease reaction was below 10%.